A masked, placebo-controlled, randomized clinical trial evaluating safety and the effect on cardiac function of low-dose rapamycin in 17 healthy client-owned dogs - Barnett, Brian G.; Wesselowski, Sonya R.; Gordon, Sonya G.; Saunders, Ashley B.; Promislow, Daniel E. L.; Schwartz, Stephen M.; Chou, Lucy; Evans, Jeremy B.; Kaeberlein, Matt; Creevy, Kate E. (Frontiers in Veterinary Science, 2023)
Geroscience studies of low-dose rapamycin in laboratory species have identified numerous benefits, including reversing age-related cardiac dysfunction. Cardiovascular benefits have been observed in dogs with ten weeks of treatment, raising questions about possible benefits and adverse effects of long-term use of low-dose rapamycin. The objectives of this study were to assess the impact of six months of low-dose rapamycin on echocardiographic indices of cardiac function in healthy dogs and to document the occurrence of adverse events. Seventeen client-owned dogs aged six to ten years, weighing 18-36 kg, and without significant systemic disease were included in a prospective, randomized, placebo-controlled, masked clinical trial. Low-dose rapamycin (0.025 mg/kg) or placebo was administered three times per week for six months. Baseline, six-month, and 12-month evaluation included physical examination, cardiology examination, and clinicopathology. Three-month evaluation included physical examination and clinicopathology. Owners completed online questionnaires every two weeks. There were no statistically significant differences in echocardiographic parameters between rapamycin and placebo groups at six or 12 months. No clinically significant adverse events occurred. In 26.8% of the bi-weekly surveys owners whose dogs received rapamycin reported perceived positive changes in behavior or health, compared to 8.1% in the placebo group (p=0.04). While no clinically significant change in cardiac function was observed in dogs treated with low-dose rapamycin, the drug was well-tolerated with no significant adverse events.